The semantics of norms mining in multi-agent systems - Ahmed Mahmoud, Moamin; Ahmad, Mohd Sharifuddin; Ahmad, Azhana; Mohd Yusoff, Mohd Zaliman; Mustapha, Aida
In this paper, we present the semantics of our proposed norms mining technique for an agent to detect the norms of a group of agents in order to comply with the group’s normative protocol. We define the semantics of entities and processes that are involved in the norms mining technique. The technique entails an agent exploiting the resources of the host system,implementing data formatting and filtering, and identifying the norms’ components that contribute to the strength of the norms to identify the group’s potential norms. We then present an algorithm of the norms mining operation and demonstrate the success of the technique in detecting the potential norms.